About a Post-processing Design of Regression-like Nonlinear Internal Models. Issue 1 (July 2017) - Bin, Michelangelo; Marconi, Lorenzo
Abstract: This paper deals with the problem of output regulation for minimum-phase single-input single-output nonlinear systems. We propose a variation of the "regression-like" design introduced by Byrnes and Isidori (2004), showing how it is possible to move the internal model from the control input to the regulation error. In this way, we obtain a post-processing scheme that more likely resembles the general design for linear systems. Although these approaches are equivalent for single-input single-output systems, a post-processing design represents a step forward in the systematic extension of the theory to the general multivariable case.